Rate of psychiatric readmissions and associated factors at Saint John of God Psychiatric Hospital in Mzuzu, Malawi - Msiska, Manson Mwachande (Department of Psychiatry and Mental Health, 2020)
Background: Globally, studies have established that 40-50% of psychiatric patients with SMDs are readmitted within one year of discharge from the acute hospital admission. Lowand middle-income countries (LMICs) such as Malawi have also reported high rates of psychiatric readmissions. This poses challenges when providing psychiatric care to patients. Most of Malawi`s health institutions, including Saint John of God Psychiatric Hospital (SJOG), rely primarily on donor funding. In order to maximise the available donor funding, there is a need to reduce readmissions resulting from modifiable or controlled factors. There are no studies in Malawi which have investigated these risk factors. The study aimed to establish the frequency of readmissions and the associated factors among patients at SJOG Psychiatric Hospital in Mzuzu, Malawi. The specific areas examined were sociodemographic and clinical-related factors associated with readmission. Methods: This was a retrospective cohort case record review study. Two hundred and seventy five clinical files of patients admitted for the first time at SJOG Psychiatric Hospital Mzuzu, Malawi between 1 January, 2014 and 31 December, 2015 were extracted. Data on socio-demographics and clinical information were collected using an extraction sheet at 3, 6 and 12 months post-discharge from the acute (first) hospital admission. Logistic regression models were developed to investigate the associations between socio-demographics, clinicalrelated factors and readmissions. Ethical approval for this study was granted by the Faculty of Health Sciences Human Research Ethics Committee at the University of Cape Town. Approval to conduct this research in Malawi was obtained from the National Health Sciences Research Ethics Committee. Results: Readmission rates of 1.5%, 4.4%, and 11.3% were found within the 3, 6 and 12 months of discharge from the acute hospital admission respectively. None of the independent variables predicted readmission within the 3 month of discharge from the acute hospital admission. In the unadjusted logistic regression model, having children (OR=0.26, 95% C.I 0.07-0.96) protected against readmissions within the 6 month of follow-up period. In the unadjusted logistic regression model, having children (OR= 0.40, 95% C.I 0.18-0.88), staying outside the hospital catchment area (OR=0.44, 95% C.I 0.20-0.96), and having insight (OR=0.22, 95% C.I 0.10-0.49) into their illness were protective factors to readmission, while taking SGAs (OR=4.67, 95% C.I 1.33-16.39) predicted readmission within the 12 month follow-up period. After adjusting for age and gender in the multivariable analysis, staying outside catchment area (OR=0.33, 95% C.I 0.14-0.79) and having insight (OR=0.19, 95% C.I 0.08-0.46) to their illness were protective factors, while taking SGAs (OR=5.29, 95% C.I 1.43-19.51) remained a predictor of readmission within 12 months of discharge from the acute admission. Conclusion: The findings of this study demonstrated that readmissions are associated with socio-demographic and clinical factors such as catchment area, patient insight into their condition and type of antipsychotics. The study identifies the need to develop interventions targeting the groups at risk of being readmitted.